Borderline ovarian tumors share familial risks with themselves and invasive cancers - Zheng, Guoqiao; Yu, Hongyao; Försti, Asta; Hemminki, Kari (Cancer epidemiology, biomarkers & prevention, 2018)
Background: Borderline ovarian tumors (BOTs) are a subgroup of ovarian malignancies with low malignant potential. Very limited earlier data are available on familial clustering of BOTs with other cancers. We aim to explore histology-specific familial associations among BOTs and associations between BOTs and any invasive cancers. - Methods: On the basis of 16.1 million individuals in the Swedish Family-Cancer Database, we estimated familial risks for overall or histology-specific patients with BOT considering both BOT and any invasive cancers in first-degree relatives (parents or siblings), as well as familial risks for invasive cancers considering family history of BOTs. - Results: A total of 4,199 BOT cases were found in the offspring generation; among them, 34 (0.8%) cases had first-degree relatives diagnosed with any BOT, and 2,489 (59.3%) cases with any invasive cancers. A family history of BOT was associated with risks for all BOTs (RR = 2.20, P < 0.001). Papillary BOT in first-degree relatives was associated with the increased risk of having the same type of BOT (RR = 10.10, P < 0.001). BOTs showed familial associations with some invasive cancers, most consistently with colorectal, ovarian, pancreatic, lung, and bone cancers, and with leukemia. In histologic analyses, associations of BOT with even rare cancers of the anus, thyroid, and endocrine glands were noted. - Conclusions: BOTs may share susceptibility with themselves and a number of invasive cancers. - Impact: These results provide insight into familial associations of BOT for the first time, which may help with the etiologic mechanism and preventive strategy of BOTs, as well as the genetic counseling for patients with BOT. Cancer Epidemiol Biomarkers Prev; 27(11); 1358-63. ©2018 AACR.